Controllable p-type doping of 2D MoS2via Sodium intercalation for optoelectronics. Issue 9 (22nd February 2023) - Ullah, Salman; Li, Ling; Wang, Yixiu; Yang, Xiaoyu; Tang, Mingwei; Xiang, Yuan; Yang, Qing
Abstract : We synthesized high-quality MoS2 flakes via the NaOH assisted CVD method. The morphological evolution of MoS2 flakes was investigated at different growth temperatures, and high-quality MoS2 were achieved with a photoresponsivity of 4.2 A W −1 and a specific detectivity of 8.1 × 10 8 Jones. Abstract : Native n-type molybdenum disulfide (MoS2 ) has drawn considerable attention as the key semiconductor for electrical, optoelectronic, and spin electronic devices. Modulating the carrier type (n to p) is important for many applications, while it is challenging to control. Practically stable doping requires substitution of host atoms with dopants such as niobium (Nb) where the doping is secured by covalent bonding. In this study, we report a controllable p-type doping strategy by sodium intercalation during the chemical vapor deposition (CVD) process. X-Ray techniques reveal that the sodium is indeed incorporated into the host MoS2 lattice and p-type carrier conduction was demonstrated by the constructed field-effect transistor. The photo response of the MoS2 photodetector was also improved approximately 2 times as compared with a pristine MoS2 photodetector by this doping method. A wide range of nanoelectronics can be envisioned from this doping route, and it is also expected that this technique demonstrated here can be generally extended to other transition metal dichalcogenides (TMDCs) for doping against their native unipolar propensity.